The Frisco kid [videorecording (DVD)] - Aldrich, Robert, 1918-1983; Wilder, Gene, 1933-2016; Ford, Harrison, 1942-; Bieri, Ramon (Warner Home Video, 2006)
It's 1850 and new rabbi Avram Belinski sets out from Philadelphia toward San Francisco. Cowpoke bandit Tom Lillard hasn't seen a rabbi before. But he knows when one needs a heap of help. And getting this tenderfoot to Frisco in one piece will cause a heap of trouble - with the law, Native Americans and a bunch of killers. Gene Wilder and Harrison Ford are one feisty team as rabbi and rescuer in this rough-'n'-ready romp that rivals Wilder's earlier Blazing Saddles in Wild West hilarity.